Techno-economic design and reliability assessment of a solar PV-battery-based green data center - Alok Kumar Shrivastav; Dipak Kumar Dash; Saumen Dhara; Pritish Ghosh (Franklin Open)
The rapid expansion of digital infrastructure has driven a surge in data center electricity consumption, intensifying concerns over carbon emissions and operational reliability. This study introduces a techno-economic framework for designing a sustainable data center powered by a solar photovoltaic (PV) and battery storage system. Reliability simulations were conducted to assess power availability and downtime, using capacity shortage and unmet load as key metrics. The proposed green data center model was benchmarked against conventional designs, with performance evaluated according to established tier reliability standards. Results indicate that integrating PV-battery systems can maintain high reliability, reduce greenhouse gas emissions, and offer stable, competitive energy costs over time. The findings support a policy shift towards renewable-based backup solutions, demonstrating that operational sustainability and reliability can be achieved without reliance on conventional generator sets.